An Analysis of the Character Education in Narrative Text of the English Textbook of Senior High School - Rahmawati; Amin, Bahrun; Muhsin, Muh. Arief (Journal of Language Testing and Assessment, 2025)
Character education has an important role in the education system besides the teacher providing material, also instilling character education in the teaching and learning process. The aims of this study was to find out the values of character education in English textbooks for tenth and eleventh grades published by the Ministry of Education and Culture in year 2017. The focus of this research is on the value of character education contained in the contents of English Textbooks based on the suitability of character education from the 2013 curriculum. The research methodology is descriptive with a qualitative approach and uses content analysis techniques. The research instruments were documentation and datasheets to present data. Source of data the researcher analyzed the narrative text in very chapter of English textbooks. The characters found are classified into 18 character values based on the 2013 curriculum and are classified into integrating character values either directly or indirectly. Based on the findings of this research, of the 18-character education values, there are only 7 character educations consisting of 4 narrative texts. The 7 values of character education are religious, honesty, hardworking, curiosity, appreciation, social care and responsibility. The most dominant characters are hardworking and social care. In addition, the direct integration technique is more dominant in this study.